1985
DOI: 10.1002/j.1460-2075.1985.tb03900.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the complex of actin and DNase I at 4.5 A resolution.

Abstract: The shape of an actin subunit has been derived from an improved 6 A map of the complex of rabbit skeletal muscle actin and bovine pancreatic DNase I obtained by X‐ray crystallographic methods. The three‐dimensional structure of DNase I determined independently at 2.5 A resolution was compared with the DNase I electron density in the actin:DNase map. The two structures are very similar at 6 A resolution thus leading to an unambiguous identification of actin as well as DNase I electron density. Furthermore the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…The shape ofthe scattering curve at larger values ofS shows that the actin molecules are not simple spheres but rather are asymmetric in shape. The calculated scattering pattern for a simple two-sphere model having approximate dimensions of actin in the DNase-actin crystal (35), yields good agreement with the experimentally observed pattern (unpublished results). Actin is filamentous in high ionic strength buffer.…”
Section: Methodssupporting
confidence: 71%
“…The shape ofthe scattering curve at larger values ofS shows that the actin molecules are not simple spheres but rather are asymmetric in shape. The calculated scattering pattern for a simple two-sphere model having approximate dimensions of actin in the DNase-actin crystal (35), yields good agreement with the experimentally observed pattern (unpublished results). Actin is filamentous in high ionic strength buffer.…”
Section: Methodssupporting
confidence: 71%
“…Modification of Tyr-53 may sterically block phalloidin binding. Tyr-53 is located at the loop region where DNase I binds [lo] and the region is at some distance from the cleft region where phalloidin binds [6] according to the X-ray crystallography model [8]. However, the size of the phalloidin molecule is sufficient for the diazonium-tetrazole modification sterically to block actin binding.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al (1984) demonstrated that in adult rat hearts, the ca-skeletal actin gene is DNase I sensitive whereas this is not the case in non-muscle cells. Moreover, there is already a low level of mRNA derived from this gene in normal adult rodent hearts Mayer et al, 1984 (Kabsch et al, 1985). The mechanical force of muscular contraction is generated at the interface between myosin heavy chain and actin in the sarcomere.…”
Section: Discussionmentioning
confidence: 99%